A CLINICAL AUDIT OF ACUTE MANAGEMENT OF STROKE-LIKE EPISODES FROM A NATIONAL MITOCHONDRIAL DISEASE CENTRE. Issue 11 (14th October 2015) - Shaw, Sarah; Ng, Yi Shiau; Whittaker, Roger; McFarland, Robert; Turnbull, Doug; Gorman, Grainne; Schaefer, Andrew
Abstract : Background: Mitochondrial encephalomyopathy, lactic acidosis and stroke-like episodes (MELAS) syndrome is an acute and severe neurological presentation most commonly associated with a point mutation in the mitochondrial tRNA Leu (UUR)gene, m.3243A>G. The onset of stroke-like episodes (SLE) is often subtle and the diagnosis is not considered until progressive encephalopathy and refractory focal seizures ensue. Objective: To review the acute management of SLE in patients with m.3243A>G related MELAS syndrome and implement revision of current centre guidelines. Method: The medical records of adult patients (over 16 years) with m.3243A>G-related MELAS syndrome were reviewed over a 20 year period (1995 to 2014). Clinical presentation, brain imaging, EEG findings and seizure management were evaluated. Results: We identified 47 SLEs occurring in 22 m.3243A>G MELAS patients (mean age 33 years). Seizures of occipital origin were most common. Time to hospital admission and investigation was highly variable. Recognition and treatment of seizure activity was often delayed. Conclusion: This audit is the first to highlight the need for early recognition and prompt management of SLE in MELAS and the role of seizure control to improve clinical outcome.